The Extremal Structures of r-Uniform Unicyclic Hypergraphs on the Signless Laplacian Estrada Index - Hongyan Lu; Zhongxun Zhu (Mathematics, 2022)
<semantics>SLEE</semantics> has various applications in a large variety of problems. The signless Laplacian Estrada index of a hypergraph H is defined as <semantics>SLEE(H)=<msubsup>∑i=1n</msubsup>eλi(Q)</semantics>, where <semantics>λ1(Q),λ2(Q),…,λn(Q)</semantics> are the eigenvalues of the signless Laplacian matrix of H. In this paper, we characterize the unique r-uniform unicyclic hypergraphs with maximum and minimum <semantics>SLEE</semantics>.